INTEGRATING MULTIMODAL ADAPTATION INTO TRANSLATOR TRAINING: A THEORETICAL RATIONALE - Sağlam, Naciye (My University, 2024)
With evolving multimedia communication, traditional translation studies focusing on fidelity are being transformed by the need for multimodal and intersemiotic approaches. Extending this discussion to translator training, this study argues for the necessity of teaching adaptation skills in the training of future translators in line with the needs of the multimedia age. By viewing translation as a process of re-creation, the study stresses the often-overlooked creative potential of translation. At this point, the inclusion of adaptations in translator training offers the opportunity to experience the inherent creative potential of translation and emphasizes the intersemiotic dimension. The paper first offers a theoretical justification for this approach, then discusses methods of implementation as well as potential benefits. Integrating adaptation into translator training can be approached theoretically, analytically, and practically. It offers advantages such as broadening the scope of translation beyond language, bridging the gap between training and market needs, and enhancing interdisciplinary knowledge.
Keywords: Adaptation; translation; translator training; intersemiotic translation; multimodal translation